Development of the inverted visceral yolk sac in three species of caviids (rodentia, caviomorpha, caviidae) - Miglino, M.; Franciolli, A. L. R.; Oliveira, M. F.; Ambrosio, C.; Bonatelli, M.; Machado, M. R. F.; Mess, A. (W B Saunders Co Ltd, 2008)
Guinea pig related rodents possess numerous derived placental characters. We attempt to identify diversity within the visceral yolk sac and its association with the chorioallantoic placenta in three species of caviids, two of them possessing a capsule formed by the decidua that covers the chorioallantoic placenta. The results verify that in early pregnancy all three species have in inverted yolk sac placenta. In advanced pregnancy the species differ: Galea spixii, as representative without a capsule, bear a yolk sac in apposition to the chorioallantoic placenta with signs of exchange activity until term. Galea is similar to other caviomorphs in this respect. In Dasyprocta leporina and Cuniculus paca, the representatives possessing a capsule, the yolk sac endoderm lacks signs of substance exchange. Evidently, the presence of a capsule prevents such ail interaction. The variations established here must be considered if animal models for human placentation are required which have restricted access to the chorioallantoic placenta from the outside. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: animal model; guinea pig; capsule; fetomaternal exchange; evolution